MicroRNA profiling in atherosclerosis, diabetes, and migraine. (17th February 2017) - Tana, Claudio; Giamberardino, Maria Adele; Cipollone, Francesco
Abstract: microRNAs (miRNAs) are a broad group of endogenous small non-coding molecules that reduce the transcription of mRNA and play a key role in post-transcriptional gene processes. miRNAs are involved in onset and progression of several human disorders such as infectious and immune non-infectious diseases, cancers, metabolic and cardiovascular disorders. They regulate the expression of gene targets (e.g. oncogenes and tumor suppressor genes) and act as gene repressors with mRNA binding and cleavage. The increasing evidence that miRNAs play a key role in the pathogenesis of cardiovascular conditions could radically change the future management approach to these disorders. This review focuses on current knowledge about the influence of miRNAs on cardiovascular disease, with particular regard to common conditions such as atherosclerosis, diabetes and migraine. Key messages: miRNAs are a group of endogenous small non-coding RNA segments measuring 19–25 nucleotides that are involved in physiologic processes and onset and progression of disorders such as infectious and immune non-infectious diseases, cancers, metabolic and cardiovascular disorders. miRNAs expression guarantees vascular integrity, by regulating apoptosis, VEGF pathway and VCAM 1 expression (−126), and is involved in atherosclerotic plaque formation process and progression. Hyperglycemia, overt diabetes, and their complications are associated with overexpression of several miRNAs. An altered expression of miRNAs has also been postulated in migraine patients, although only a few preliminary studies have so far been performed with this respect.